Hasil Laboratorium Kelayakan Sumber Mata Air Cikoneng Kabupaten Garut - Roby Ramda Nurputra; Adi Susetyaningsih; Eko Walujodjati (Institut Teknologi Garut, 2022)
The source of Curug Cikoneng spring water is a type of small spring, while the type of water is a type of fractured spring, which emerges from rock fractures. So far, water from the Cikoneng waterfall has not been optimally used as a source of raw water for the people of Pasawahan village because the water has a sour taste. This study aims to determine the quality of water sourced from the Curug Cikoneng spring as a need for residents in Pasawahan Village, Tarogong Kaler District, Garut Regency, West Java Province. The method used is descriptive method with the object of research is 1 spring in the village of Pasawahan Kaki Gunung Guntur. Data collection techniques by means of observation, observation, sampling at several points, namely Jaba Tonggoh, Jaba Lebak and PLP Citiis, sample testing was carried out at the Garut Kesda Laboratory using reference to PERMENKES RI NO.492/MENKES/PER/IV/2010, analyzing samples and interviews. The results showed that for the three sources, sample 1 (Jaba Tonggoh) and sample 3 (PLP Citiis) the water is odorless, has a clear color and the turbidity level is below the maximum limit, while sample 2 (Jaba Lebak) the water is odorless but has a light yellow color and has turbidity level of 32.38 NTU, but for the three samples it has a sour taste. pH at (sample 1) 3.5, (sample 2) 6.6 and (sample 3) 3.6. Fe (Iron) levels in (sample 1) 3.49 mg/l, (sample 2) 0.63 mg/l and (sample 3) 0.61 mg/l. Manganese levels in (sample 1) 0.63 mg/l, (sample 2) 0.48 mg/l and (sample 3) 0.58 mg/l. Sulfate levels (sample 1) 800 mg/l, (sample 2) 520 mg/l and (sample 3) 790 mg/l. The number of coliform bacteria sample 1 (15), sample 2 (38) and sample 3 (≥240). From the results of research that has been done, Curug Cikoneng springs are not suitable for consumption.